Effect of rotational grazing by yearlings on early-intensive, double-stocked, native grass - Brazle, F.; Kuhl, Gerry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Continuous, early-intensive (double-stocked) grazing vs. early-intensive grazing using a two-pasture, 16 to 18-day rotation were compared in three experiments. No significant differences were found (P>.15) in daily gains of stockers or forage remaining after the 2 ½ month grazing season
Keywords: Beef; Rotational grazing; Yearlings; Native grass